SUSCEPTIBLE-INFECTED-REMOVED MODEL OF AIDS INCIDENCE IN THE PHILIPPINES - Batara, Annah Bernice L.; Gayo, Jhoanna Lea P.; Bueno, Aldous Cesar F. (Journal of Technology Management and Business, 2018)
Acquired Immunodeficiency Syndrome (AIDS) being one of the top 10 most communicable diseases, according to the Alameda County Public Health Department. It is caused by the Human Immunodeficiency Virus (HIV). This virus is also known to have no ways to be removed inside the infected human body yet. The spread of this disease in the Philippines was studied using the Susceptible-Infected-Removed Model which is a modification of the usual Susceptible-Infected-Recovered Model for no data show a person recover from AIDS. In this model, the populations of the Philippines from 1984 to 2010 were gathered. Two methods were used to derive the model, first by curve fitting and the other by computing the infection rate and the removal rate. The number of infected by AIDS and death toll for 2011 to 2016 were predicted using the obtained functions and rates.